10.1093/gao/9781884446054.013.7002292402 (Inactive DOIs, 2018)
BACKGROUND: Online hemodiafiltration (HDF) enhances the removal of middle molecules, including large-middle molecules, through the combined action of diffusion and convection. Randomized controlled trials (RCTs) and individual participant data (IPD) meta-analyses demonstrate improved cardiovascular outcomes and, importantly, a reduction in all-cause mortality when HDF is delivered with sufficiently high convective volumes in post-dilution mode. These findings underscore that an adequate convective dose is a critical determinant of clinical benefits compared to high-flux hemodialysis (HD). However, translation into consistent clinical practice remains heterogeneous. Therefore, the Italian Society of Nephrology convened an international, multidisciplinary panel to synthesize randomized evidence comparing online post-dilution HDF with high-flux HD in adults receiving maintenance hemodialysis. METHODS: The critical outcomes included all-cause and cardiovascular mortality, whereas the important outcomes included selected patient-reported health domains, including physical function, patient-perceived cognitive function, pain interference, social participation, and health-related quality of life. The certainty of the evidence was appraised using the GRADE methodology. Structured guidance recommendations and best practice statements were developed through a consensus. Sensitivity analyses were performed to assess the robustness of the observed mortality effect. RESULTS: High-volume post-dilution HDF reduces all-cause mortality (hazard ratio 0.84; 95% CI 0 74-0.95; moderate-certainty evidence) and cardiovascular mortality (hazard ratio 0.78, 95% CI 0.64-0.96; moderate-certainty evidence; data from an individual participant data analysis of trials of high volume HDF versus high-flux HD). Emerging evidence suggests slower deterioration in selected patient-reported domains, including physical function, patient-perceived cognitive function, pain interference, and social participation (low-certainty evidence). Safety with on-line post-dilution HDF has been demonstrated to be similar to that of high-flux HD. CONCLUSIONS: Online post-dilution HDF should be regarded as a dose-dependent therapy. We recommend its use to reduce cardiovascular mortality and suggest high-volume HDF to reduce all-cause mortality and slow deterioration in selected patient-reported health domains. Effective implementation in clinical practice requires a targeted and individualized approach with careful optimization and monitoring of convective volume, along with appropriate treatment time, blood-flow rate, supporting infrastructure, and consideration of patient preferences. This guidance provides evidence-based recommendations and best practice statements for its use.